EFFECTS OF SEDIMENT AGGREGATE SIZE ON DRM INTENSITY: A NEW THEORY - Katari K.; Bloxham J. (My University, 2001)
Previously, the acquisition of depositional remanent magnetism (DRM) in redeposition experiments has been described as a balance between the alignment of magnetic moments by the imposed magnetic field and the misaligning effects of Brownian motion, an approach that ignores interactions between sediment particles. Inter-particle attractions due to electrostatic or van der Waals forces, or biologically mediated flocculation, lead to the formation of aggregates, which prevent the settling of individual grains. We propose a new model in which we examine the angular momentum balance on a clay-magnetite aggregate, which can be tens of micrometers in diameter, as opposed to an individual grain of single-domain magnetite, which is usually less than 1 μm in diameter. Viscous drag becomes important for these large aggregates and larger magnetic fields are necessary to bring their moments into alignment. We model the acquisition of DRM by assuming a log-normal size distribution of flocs, all of which have the same magnetic moment. The under-saturation of magnetic intensity in laboratory DRM experiments is explained by the larger viscous drag encountered by the larger aggregates which prevents perfect alignment with the applied magnetic field.
Keywords: DEPOSITIONAL REMANENT MAGNETIZATION; MAGNETIC INTENSITY; FLOCCULATION; SEDIMENTS; NONMAGNETIC MINERALS